Global Climate Change as a Driver of Bottom-Up and Top-Down Factors in Agricultural Landscapes and the Fate of Host-Parasitoid Interactions - Chidawanyika, Frank; Mudavanhu, Pride; Nyamukondiwa, Casper (Frontiers in Ecology and Evolution, 2019)
The global climate is rapidly changing and the evidence is increasingly manifesting across various biological systems. For arthropods, several studies have demonstrated how changing climates affect their distribution through phenological and physiological responses, largely focusing on various organismal fitness parameters. However, the net-effect of the changing climate among ecological communities may be mediated by the feedback pathways among interacting trophic groups under environmental change. For agroecosystems, the maintenance of the integrity of trophic interactions even under climate variability is a high priority. This is even more important in this era where there is advocacy for sustainable agriculture, with higher emphasis on environmentally benign methods. For this reason, pest management in food production systems using biological control (especially use of parasitoid antagonists) has come to the forefront. In this review, we give an overview of the diversity of physiological responses among host insect and parasitoid populations and how this may influence their interactions. We highlight how climate change may modify bottom-up and top-down factors among agroecosystems with a particular focus on plant-insect host-parasitoid tritrophic interactions. We also outline how habitat management may influence arthropod population dynamics and how it can be manipulated to improve on-farm climate resilience and parasitoid conservation. We wrap-up by highlighting how the application of knowledge of conservation biodiversity, designing of multifunctional resilient landscapes, and evolutionary physiology of arthropods under thermal stress may be used to improve the fitness of mass-reared parasitoids (in or ex situ) for the improvement in efficacy of parasitoids ecosystem services under thermally stressful environments